Variable phase signal demodulator - WOODWORTH; DONALD J; MAGIN; GREGORY A (1987)
A dual conversion variable bandwidth telemetry receiver employs a phase locked loop which controls the second local oscillator to maintain lock on the carrier frequency; the phase locked loop employing a loop filter with a variable time constant integrator, the time constant of which can be varied as a function of receiver bandwidth and the integrator with its associated capacitor and resistor banks being employed in a sweep, i.e. search, oscillator circuit enabled when the carrier signal is lost. A coherent double-balanced mixer is employed to detect carrier lock and if lock is lost but the carrier is still detected, a rapid response anti-sideband circuit in the phase detector of the phase locked loop is employed to suppress the sidebands and greatly increase the probability of relocking on the carrier. A synchronous AM detector employs quadrature IF and reference signals at the same frequency to produce a dc signal when phase lock occurs; the signal falling rapidly upon loss of lock. The synchronous AM detector employs a variable time constant integrator for eliminating noise above a low frequency to accommodate carrier fading, said integrator being located in an AGC circuit of an amplifier feeding a balanced mixer to hold the IF at a constant level, thus permitting detection of carrier signals at a carrier to noise ratio as low as a -20 dB. The AM detector also produces a substantially exact reproduction of the AM signal for use elsewhere in the receiver.